Association between gut microbiota and bone metabolism: Insights from bibliometric analysis - Zhang, Zhanrong; Zhang, Zheng; Shu, Haoming; Meng, Yichen; Lin, Tao; Ma, Jun; Zhao, Jianquan; Zhou, Xuhui (Frontiers in Physiology, 2023)
Gut microbiota has already been reported to participate in bone metabolism. However, no article has reported the quantitative and qualitative analysis in this crossing field. The present study aims to analyze the current international research trends and demonstrate the possible hotspots in the recent decade by bibliometrics. In this study, we screened out 938 articles meeting the standard from 2001 to 2021 in the Web of Science Core Collection database. The bibliometric analyses were performed and visualized by Excel, Citespace and VOSviewer. Generally, the annual number of published literature in this field assumes the trend of escalation. The United States was the country with the largest number of publications, accounting for 30.4% of the total. Michigan State University and Sichuan University had the largest publications number, while the Michigan State University had the highest average number of citations at 60.00. Nutrients published 49 articles, ranking first while Journal of Bone and Mineral Research had the highest average number of citations at 13.36. Narayanan Parameswaran from Michigan State Univ, Roberto Pacifici from Emory Univ, and Christopher Hernandez from Cornell Univ were the three professors that made the largest contribution to this field. The frequency analysis showed that inflammation (148), obesity (86), and probiotics (81) are keywords with the highest focus. Moreover, keywords cluster analysis and keywords burst analysis showed that “inflammation”, “obesity” and “probiotics” were the most researched topics in the field of gut microbiota and bone metabolism. Scientific publications related to gut microbiota and bone metabolism has continuously rising from 2001 to 2021. The underlying mechanism has been widely studied in the past few years, and factors affecting the alterations of the gut microbiota as well as probiotic treatment are emerging as new research trends.